An Additional Information of Tarenna (Rubiaceae) in Madura Island - Indah, Novita; Bagus Setiawan, Ashari (Jurnal Riset Biologi dan Aplikasinya, 2022)
Tarenna is a genus of relatives of Ixora which is found in forests. Tarenna is different from Ixora which is known as an ornamental plant. The purpose of this study was to find the genus Tarenna in Madura natural habitat to preserved or conserved before this genus became extinct. Observations were made on morphological characters. The morphological characteristics observed included: stature, stems, leaves, inflorescences, flowers, fruits, and seeds. Ixora has a corolla of various flowers while Tarenna only has a white corolla but smells good. Recent exploration and collection of Tarenna in Madura Island indicated that two species are a new record for Java and Madura Island, namely T. costata and T. fragrans. Existence of T. costata in this area not only as a new record for Madura Island, but also as a new record for Java. Tarenna fragrans was firstly reported in Madura Island as a new distributional record for this area. An updated of identification key, several descriptions, and documentations, as well as a distributional map are provided.